2013
DOI: 10.1080/10810730.2013.798374
|View full text |Cite
|
Sign up to set email alerts
|

Employing Virtual Advisors in Preventive Care for Underserved Communities: Results From the COMPASS Study

Abstract: Electronically delivered health promotion programs that are aimed primarily at educated, health-literate individuals have proliferated, raising concerns that such trends could exacerbate health disparities in the United States and elsewhere. The efficacy of a culturally and linguistically adapted virtual advisor that provides tailored physical activity advice and support was tested in low-income older adults. Forty inactive adults (92.5% Latino) 55 years of age and older were randomized to a 4-month virtual ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
140
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 50 publications
5
140
0
3
Order By: Relevance
“…8, 9, 10 Conversational agents are a logical option to deliver PCH information as they can reach a large audience while providing high user acceptability through culturally-appropriate content and information appropriate to those with low health literacy. 11, 12 AA women may benefit from conversational agents due to disparities in health literacy levels as according to the 2006 report by the U.S. Department of Education, 58 percent of AA adults possess Below Basic or Basic health literacy, compared to 28 percent of white adults. 13 There is also evidence that clinicians are more verbally-dominant and less patient-centered with AA patients, 14 and that these systems can overcome clinician time constraints 15 and assist in delivering recommended preventive care.…”
Section: Introductionmentioning
confidence: 99%
“…8, 9, 10 Conversational agents are a logical option to deliver PCH information as they can reach a large audience while providing high user acceptability through culturally-appropriate content and information appropriate to those with low health literacy. 11, 12 AA women may benefit from conversational agents due to disparities in health literacy levels as according to the 2006 report by the U.S. Department of Education, 58 percent of AA adults possess Below Basic or Basic health literacy, compared to 28 percent of white adults. 13 There is also evidence that clinicians are more verbally-dominant and less patient-centered with AA patients, 14 and that these systems can overcome clinician time constraints 15 and assist in delivering recommended preventive care.…”
Section: Introductionmentioning
confidence: 99%
“…24-27 Use of the relational agent system requires very minimal reading skills. We have previously shown that the interface can be designed in a manner that is usable for people with limited health literacy, limited reading capacity, and no prior computer experience, 19,22,28,29 which makes it a potentially useful platform to collecting detailed family history information in an electronic format.…”
Section: Introductionmentioning
confidence: 99%
“…Primary task support features such as tailoring and monitoring are often present together with dialogue support features such as reminder, rewards and praise. An example of this is "user specific goal setting" present with "text based positive reinforcement" [49]. Applications that included self-monitoring feature generally included also a feedback mechanism that allowed the user to review their data [34].…”
mentioning
confidence: 99%